Molecular Action of Lenalidomide in Lymphocytes and Hematologic Malignancies - Jessica M. McDaniel; Javier Pinilla-Ibarz; P. K. Epling-Burnette (Advances in Hematology)
The immunomodulatory agent, lenalidomide, is a structural analogue of thalidomide approved by the US Food and Drug Administration for the treatment of myelodysplastic syndrome (MDS) and multiple myeloma (MM). This agent is also currently under active investigation for the treatment of chronic lymphocytic leukemia (CLL) and non-Hodgkin’s lymphoma (NHL), as well as in drug combinations for some solid tumors and mantle cell lymphoma (MCL). Although treatment with lenalidomide has translated into a significant extension in overall survival in MM and MDS and has superior safety and efficacy relative to thalidomide, the mechanism of action as it relates to immune modulation remains elusive. Based on preclinical models and clinical trials, lenalidomide, as well as other structural thalidomide derivatives, enhances the proliferative and functional capacity of T-lymphocytes and amplifies costimulatory signaling pathways that activate effector responses and suppress inflammation. This paper summarizes our current understanding of T- and natural killer (NK) cell pathways that are modified by lenalidomide in hematopoietic neoplasms to inform future decisions about potential combination therapies.